2007
DOI: 10.1002/joc.1562
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of climatological data in Jordan

Abstract: This paper evaluates climate variability over Jordan by considering temporal and spatial variations on the basis of annual and seasonal meteorological variables including precipitation, relative humidity (RH), maximum and minimum temperatures over 30 years at 16 representative observation stations over the whole country. The assessments are based on the statistical parameters such as the averages, coefficient of variation and skewness (SK). These parameters are mapped through the Kriging regional variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 3 publications
1
21
0
Order By: Relevance
“…Mean annual rainfall and mean maximum daily rainfall are increasing but statistically not significant in two stations (RAS and JOU) in the subhumid zone and this is consistent with the findings with similar nearby subhumid regions such as central western parts of the Jordan river (Alpert et al, 2002;Wettenberg et al, 2007;Yusef et al, 2009). Mean annual rainfall in the semi-arid zone shows a general nonsignificant decreasing trend and this agrees with some earlier studies which reported nonsignificant decrease in mean daily and monthly rainfall (Freiwan and Kadioglu, 2008a;2008b;Ghanem, 2011). But, this study shows that maximum daily rainfall is a more sensitive rainfall index to variability than other rainfall indices, especially in the semi arid regions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Mean annual rainfall and mean maximum daily rainfall are increasing but statistically not significant in two stations (RAS and JOU) in the subhumid zone and this is consistent with the findings with similar nearby subhumid regions such as central western parts of the Jordan river (Alpert et al, 2002;Wettenberg et al, 2007;Yusef et al, 2009). Mean annual rainfall in the semi-arid zone shows a general nonsignificant decreasing trend and this agrees with some earlier studies which reported nonsignificant decrease in mean daily and monthly rainfall (Freiwan and Kadioglu, 2008a;2008b;Ghanem, 2011). But, this study shows that maximum daily rainfall is a more sensitive rainfall index to variability than other rainfall indices, especially in the semi arid regions.…”
Section: Discussionsupporting
confidence: 91%
“…In general, no statistically significant trend has been found (Freiwan and Kadioglu, 2008a;2008b);Ghanem, 2011). Decline in the total rainfall and number of rain days in the second half of the past century has been reported in Jordan (Smadi and Zghoul, 2006).…”
Section: Introductionmentioning
confidence: 94%
“…Spatial variability in the precipitation data of Jordan was analyzed by Shehadeh (1976) and very recently by Freiwan and Kadioglu (2008a), periodicity by Tarawneh and Kadioglu (2003), and structural characteristics by Dahamsheh and Aksoy (2007) and Freiwan and Kadioglu (2008b).…”
Section: Study Area and Datamentioning
confidence: 99%
“…Israel in the Middle East has been studied widely (Ben-Gai et al, 1993;1994;1998;Steinberger and Gazit-Yaari, 1996;Krichak et al, 2000) while studies devoted to the analysis of precipitation data in Jordan are rare. Variability in the precipitation data of Jordan was analysed by Shehadeh (1976) and Freiwan and Kadioglu (2007a), periodicity by Tarawneh and Kadioglu (2003), and the structural characteristics by Dahamsheh and Aksoy (2007) and Freiwan and Kadioglu (2007b).…”
Section: Introductionmentioning
confidence: 99%